Academic Probation in Colleges of Education in North-Western Nigeria: Implementation and Impact - Mustapha Sumaila Sani; Sunday Akanmu Okegbile; Abdulkarim Bello Norde; John Eze Edeh (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
This study, which was guided by three research questions, used the qualitative method of a case study to explore the level of implementation of the academic probation policy in North-Western Nigeria, and how it impacted on academic performance of students. The population for this study included examination officers. The population is not intended to statistically represent a group on campus but is instead a group of individuals who shared a specific educational experience. Data was collected through interviews with Examination officers in the selected colleges and analyzed using the thematic data analysis technique. Findings of the study revealed that the colleges are implementing probation on students whose CGPA is less than 1:00 point in line with NCCE probation policy. It further revealed that the implementation of probation has positively impacted the probating students by making them work harder to remedy their deficiencies, improve their performances and subsequently pass their examinations to meet their graduation requirements. The study also found out that most of the probating students see probation as a punishment, a very difficult process, and an unpleasant situation. The study, therefore, recommended that Guidance and Counselling Units of colleges of education should always guide probating students on the importance of the policy for the improvement of their academic performances, and colleges of education should always make sure that experienced and qualified lecturers handle students on probation.